2013
DOI: 10.1002/jso.23344
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the histological determination of microRNAs in the screening, diagnosis and prognosis of colorectal cancer

Abstract: MicroRNAs are short non-coding RNA molecules that participate in the regulation of gene expression. Several studies have demonstrated the involvement of microRNAs in oncogenesis and a variety of physiological functions. We conducted a literature review of studies that evaluated histological microRNAs in colorectal cancer. Although additional clinical studies are required to substantiate the relationship between microRNAs and colorectal cancer, there is preliminary evidence that microRNAs are related to the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
14

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
4
0
14
Order By: Relevance
“…Nevertheless, microRNAs differentially expressed in long and short survivors but not part of the signature are likely to contribute to the progression of the disease. This is reflected by the fact that many of the microRNAs identified in this study have been linked to development (Esquela‐Kerscher and Slack, 2006; Garzon et al., 2009; Ruan et al., 2009; Stahlhut and Slack, 2013) and prognosis (Kneitz et al., 2014; Menendez et al., 2013; Nair et al., 2012; Qu et al., 2014) of other cancers. For example miR‐21‐5p, miR‐221‐3p and members of the miR‐17∼92 cluster (miR‐17‐5p, miR‐19b‐3p, and miR‐20a‐5p) have been shown to regulate PTEN protein expression, and modulate the PI3K/Akt signaling axis (Concepcion et al., 2012; Pan et al., 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, microRNAs differentially expressed in long and short survivors but not part of the signature are likely to contribute to the progression of the disease. This is reflected by the fact that many of the microRNAs identified in this study have been linked to development (Esquela‐Kerscher and Slack, 2006; Garzon et al., 2009; Ruan et al., 2009; Stahlhut and Slack, 2013) and prognosis (Kneitz et al., 2014; Menendez et al., 2013; Nair et al., 2012; Qu et al., 2014) of other cancers. For example miR‐21‐5p, miR‐221‐3p and members of the miR‐17∼92 cluster (miR‐17‐5p, miR‐19b‐3p, and miR‐20a‐5p) have been shown to regulate PTEN protein expression, and modulate the PI3K/Akt signaling axis (Concepcion et al., 2012; Pan et al., 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, several studies have indicated that miRNA extracted from blood samples could be useful for the diagnosis of CRC [23, 24]. In addition, several studies have indicated that miRNAs may be potential biomarkers of either CRC metastases or recurrence [25, 26]. In the present study, we focused on the relationship between the expression of miRNA extracted from CRC tissue samples and its use as a predictive marker of recurrence.…”
Section: Discussionmentioning
confidence: 96%
“…Besides having a functional role in the initiation and progression of colorectal cancer, miRNAs are about to introduce a new era of diagnostic, prognostic and therapeutic modalities for this human malignancy (43)(44)(45). These small molecules are being intensively evaluated as biomarkers and therapeutic targets for colorectal cancer (46), as their expression patterns are subjected to remarkable alterations in tumor tissues (45), blood (plasma) (47,48) and feces (49)(50)(51). In addition to miRNA expression signatures (48), miRNA methylation signatures may provide candidate biomarkers for the detection of malignant colonocytes, since miRNAs are epigenetically modified in CRC (52,53).…”
Section: Discussionmentioning
confidence: 99%